IMPLEMENTATION OF PPTP AND BCP WITH INTER- VLAN ON THE TOPOLOGY THAT USES 2 ISP AS INTER-DIVISION CONNECTORS (Case Study: PT Kenari Djaja Prima) - Jimmy Gunawan; Halim Agung (Jurnal Algoritma, Logika dan Komputasi, 2019)
PT Kenari Djaja Prima will create a tunnel between branch offices located far from the central office so that these two offices can retrieve data on the server. As well as forming a local network between branch offices and centers. From the problem, the authors conducted a study and proposed using VLANs to divide divisions, and the tunnel method in the form of PPTP as encryption tunnel to connect with branch offices and BCP methods to forward ethernet packets so that the IP segmentation of headquarters with branches could be connected. From the results of this study, the average maximum Mbps obtained from downloads is 25.87 Mb, the average is at least 1.19 Mb, the average speed is 15.24 Mb, the average time is one minute and thirty seven seconds, and the average delay is 200.28 MS. The conclusion obtained in this study is that division of divisions with VLANs can be overcome, and between divisions have their own VLAN IDs, and can communicate with each other using Inter-VLAN. And use tunnels to connect branch offices with headquarters using PPTP. PPTP as tunnel encryption, EoIP as an ethernet connector and as a VLAN distribution between headquarters and branches. So that the data will be safe until the destination.Keywords: PPTP, QoS, VLAN, Inter-VLAN